Determinan Pendapatan Perempuan, Tingkat Pendidikan dan Laju Pertumbuhan Ekonomi terhadap Kemiskinan di Provinsi Nusa Tenggara Timur (NTT) - Damayanti, Alfina; Muslinawati, Retno; Susilo, Joko Hadi (Universitas Batanghari Jambi, 2025)
This research aims to analyze the determinants of women's income, education level and economic growth rate on poverty in East Nusa Tenggara Province using panel data from 21 districts and 1 city during the period 2017 – 2023. This research adopts a panel regression model with the Common Effect Model method ( CEM), Fixed Effect Model (FEM) and Random Effect Model (REM) with the selection of the best model through the Chow and Hausman tests. The results of this research provide interesting findings. Even though women's education levels are proven to be positively correlated with poverty reduction in East Nusa Tenggara (NTT) Province, women's income and the rate of economic growth do not show a significant influence.